Palmer, P. J. (2017). The courage to teach: Exploring the inner landscape of a teacher’s life. San Francisco, CA: John Wiley & Sons. (Journal of Applied Learning and Teaching, 2018)
As an educator with two decades of teaching experience, the last thing I need to be told is to re-examine my career as a teacher, reflect on my life and passion, and, if possible, return to my true self to be a good teacher. However, this is exactly what Parker Palmer advocates in his book. Palmer believes, “…good teaching cannot be reduced to technique…” (10), just as you don’t expect using role-playing to teach organic chemistry, he adds.Parker J. Palmer is a writer, speaker and activist who focuses on issues in education, spirituality, and social reform. He holds a Ph.D. in sociology from the University of California at Berkeley.According to Palmer, it is no secret that most teachers suffer from bureaucratic harassment, put up with unreasonable expectations from parents and institutions, are at the mercy of student ratings, are unappreciated by the public and are poorly compensated. It is little wonder some good educators have given up altogether even the pretence of teaching.